Rainfall and temperature variations overtime(1986-2015) in Siaya County, Kenya. - Abura, Beatrice A.; Hayombe, Patrick O.; Tonui, Warkach K. (International Journal of Education and Research, 2017)
This study was carried out in Siaya County. The purpose of the study was to analyze the variations on temperature and rainfall overtime (1986-2015) in Siaya County. The secondary data used for the Mann-Kendall test was attained from the metrological department of Siaya County. The Mann-Kendall results from mean annual average temperature, and mean annual rainfall indicated that Siaya County had no significant trends on rainfall and temperature over time (1986-2015) but it had variation on the same as consecutive years varied on the temperatures and rainfall levels. The metrological department of Siaya County should find a way of ensuring that rainfall and temperature variations County data is made available to community members as it can help in developing resilience strategies to climate change and knowing how best they can manage their livelihoods even with the continuation of the variations.
Keywords: Rainfall; Temperature; Variation; Siaya; County; Kenya